2013
DOI: 10.1088/0264-9381/31/2/025018
|View full text |Cite
|
Sign up to set email alerts
|

Localized fermions on domain walls and extended supersymmetric quantum mechanics

Abstract: We study fermionic fields localized on topologically unstable domain walls bounded by strings in a grand unified theory theoretical framework. Particularly, we found that the localized fermionic degrees of freedom, which are up and down quarks as well as charged leptons, are connected to three independent N = 2, d = 1 supersymmetric quantum mechanics algebras. As we demonstrate, these algebras can be combined to form higher order representations of N = 2, d = 1 supersymmetry. Due to the uniform coupling of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 69 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…In addition, the system also has three distinct N = 4, d = 1 supersymmetries, with non-trivial topological charges, as can be seen in Table 2 In addition, we studied some dualities of the one dimensional superalgebras we found. The present work is a generalization of a previous work [4], where we found that a N = 4, d = 1 supersymmetry underlies the fermionic system that is composed by the lepton and down quark, in the particular case of gauge coupling unification. We believe that the work we presented in the present article generalizes the work of the previous one and also motivates some questions, with regards the existence of non-trivial topological charges.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In addition, the system also has three distinct N = 4, d = 1 supersymmetries, with non-trivial topological charges, as can be seen in Table 2 In addition, we studied some dualities of the one dimensional superalgebras we found. The present work is a generalization of a previous work [4], where we found that a N = 4, d = 1 supersymmetry underlies the fermionic system that is composed by the lepton and down quark, in the particular case of gauge coupling unification. We believe that the work we presented in the present article generalizes the work of the previous one and also motivates some questions, with regards the existence of non-trivial topological charges.…”
Section: Discussionsupporting
confidence: 60%
“…In a previous paper [4] we demonstrated that the fermionic zero modes localized on topologically unstable domain walls bounded by strings in a grand unified theory theoretical framework, can be connected to three independent N = 2, d = 1 supersymmetric quantum mechanics algebras (for reviews and important papers on supersymmetry see [?, 5-14]). The fermions we took into account were up quarks, down quarks and also charged leptons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an elegant method is given in [38]. First, let us recall the general form of RE [38][39][40][41][42][43][44][45][46], which is given by dK dx…”
Section: Construction Of Coherent State For Real Pdemmentioning
confidence: 99%
“…Supersymmetric (SUSY) quantum mechanics [1] has shown to be a useful arena in which to invesitigate various mathematical and physical properties of symmetry operators throughout diverse fields of theoretical physics [2][3][4][5][6]. Here, we extend the available symmetry operators to include the modular operators first introduced by Tomita and Takesaki [7].…”
Section: Introductionmentioning
confidence: 99%